From expectations to experience: prioritizing quality improvement in inpatient nursing care through importance–performance analysis - Hermin Husaeni; Boby Nurmagandi; Nur Amaliah Sawal; Aco Mursid; Muhammad Amin R; Ika Muzdali; Maryati Maryati (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: The quality of nursing services plays a crucial role in shaping patients’ experiences and overall hospital service quality. In inpatient wards, nurses maintain the most frequent interaction with patients, making their caring behavior, communication, and responsiveness essential determinants of patient-centered care. However, many evaluations of nursing services focus mainly on overall satisfaction scores and fail to identify which service attributes require priority improvement. Therefore, this study aimed to analyze the gap between the importance and performance of nursing service attributes in inpatient wards and to identify priority areas for quality improvement using the Importance–Performance Analysis (IPA) approach. Research Methodology: This study employed a quantitative descriptive–analytic design with a cross‑sectional approach. The research was conducted in hospital inpatient wards involving 201 adult patients selected through purposive sampling. Data were collected using a structured questionnaire developed based on the SERVQUAL framework and Swanson’s Theory of Caring, measuring patients perceived importance and performance of nursing service attributes. Instrument validity was tested using Pearson Product Moment correlation and reliability using Cronbach’s Alpha. Data analysis was performed using mean score comparison, gap analysis (Performance − Importance), and Importance–Performance Analysis (IPA) matrix mapping with IBM SPSS and Microsoft Excel. Results: The findings indicated that most nursing service attributes were perceived as highly important by patients, with an overall mean importance score of 3.69 compared with a lower mean performance score of 2.79. Negative gap values were observed across nearly all service attributes, indicating that nursing service performance had not fully met patient expectations. The largest gaps were identified in caring-related attributes, particularly therapeutic communication, individualized attention, emotional support, and responsiveness to patient needs. IPA matrix mapping showed that several relational attributes were located in the high‑priority improvement quadrant, while aspects related to professional competence, patient safety, and trust were positioned within the key strength’s quadrant. Conclusion: The study demonstrates that relational aspects of nursing care particularly communication, empathy, and responsiveness represent the primary areas requiring quality improvement in inpatient services. Strengthening therapeutic interaction, improving service consistency, and ensuring nurse availability are essential strategies to enhance patient-centered nursing care and sustain continuous quality improvement in hospital settings.